2015
DOI: 10.18826/ijsets.95709
|View full text |Cite
|
Sign up to set email alerts
|

Ortaöğreti̇m 9. Sinif Öğrenci̇leri̇ni̇n Beden Eği̇ti̇mi̇ Ve Spora İli̇şki̇n Tutumlari İle Okula Yabacilaşma Düzeyleri̇ Arasindaki̇ İli̇şki̇ni̇n Beli̇rlenmesi̇

Abstract: Ortaöğretim 9.sınıf öğrencilerinin beden eğitimi ve spora ilişkin tutumları ile okula yabancılaşma düzeylerinin bazı değişkenler ile ilişkisini belirlemektir. Materyal ve Yöntem: İlişkisel tarama modelinin kullanıldığı bu çalışma Balıkesir il merkezinde tesadüfi örneklem medotu ile seçilen ortaöğretim kurumlarında öğrenim gören 9.sınıf öğrencilerinden 451 kadın ve 398 erkek olmak üzere toplam 849 orta öğretim öğrencisi ile yürütülmüştür. Araştırmada veri toplamak amacıyla; kişisel bilgi formu, 9.sınıf öğrencil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
4
1
5
Order By: Relevance
“…In the study of Yanık and Çamlıyer (2015), who reported opposite results of the results of this study and other studies, there was no significant difference in attitudes of participants towards physical education lesson and sports according to gender. In the study of Göksel and Caz (2016), no statistically significant difference was found between male and female students.…”
Section: Discussioncontrasting
confidence: 94%
“…In the study of Yanık and Çamlıyer (2015), who reported opposite results of the results of this study and other studies, there was no significant difference in attitudes of participants towards physical education lesson and sports according to gender. In the study of Göksel and Caz (2016), no statistically significant difference was found between male and female students.…”
Section: Discussioncontrasting
confidence: 94%
“…Yaptığımız çalışmada cinsiyet açısından beden eğitimi ve spora yönelik tutum değişikliği görülmemiştir. Literatüre bakıldığında da benzer şekilde spora yönelik tutumun cinsiyet değişkenine göre farklılaşmadığı ve cinsiyetin sportif tutum üzerinde ayırt edici bir değişken olmadığı bulunmuştur (Belli vd., 2019;Göksel vd., 2017;Göksel ve Caz, 2016;Gürbüz ve Özkan, 2012;Keskin, 2015;Koçak, Tuncel ve Tuncel, 2015;Van Wersch, Trew & Turner, 1992;Yanık ve Çamlıyer, 2015). Bu sonuçların aksine yapılan bazı çalışmalarda cinsiyet değişkenine göre erkeklerin kadınlara oranla daha fazla spora yönelik pozitif bir tutum sergiledikleri belirlenmiştir (Balyan, Balyan ve Kiremitçi, 2012;Çelik ve Pulur;Kangalgil vd., 2006;Koçak, 2014;Şiko ve Demirhan 2002;Tavlaş, 2012;Türkeli vd., 2017;Türkmen vd., 2016).…”
Section: Discussionunclassified
“…Thus, Physical Education and Sports lesson programs applied in secondary schools should meet children's need to move and to enable the organism to develop and it should eliminate the immobility of modern life and to make everyone influenced by the program to participate in the process to develop (Sunay and Sunay, 1996). Within the social structure, schools are responsible for educating individuals and to prepare children and young individuals to the future in the best way by making them understand the environment they live in (Yanık and Çamlıyer, 2015). In general, students form positive point of view about their teachers and classmates during their school life.…”
Section: Turkish Studies Volume 14 Issue 6 2019mentioning
confidence: 99%